2007
DOI: 10.1186/1471-2105-8-368
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of algorithms for high throughput detection of genomic copy number variation in oligonucleotide microarray data

Abstract: Background: Genomic deletions and duplications are important in the pathogenesis of diseases, such as cancer and mental retardation, and have recently been shown to occur frequently in unaffected individuals as polymorphisms. Affymetrix GeneChip whole genome sampling analysis (WGSA) combined with 100 K single nucleotide polymorphism (SNP) genotyping arrays is one of several microarray-based approaches that are now being used to detect such structural genomic changes. The popularity of this technology and its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 27 publications
9
52
0
Order By: Relevance
“…Precise mapping of CNVs is important when determining overlap with CNV in parents and control cohorts, as well as for determining the functional content in these regions and performing detailed genotype-phenotype correlations. Our results and those of others [Baross et al, 2007;Friedman et al, 2006;Pinto et al, 2007] indicate that further optimization of automatic copy number detection algorithms is required for optimal CNV identification and characterization via genome wide microarray platforms. At present, we suggest performing CNV identification with two software packages and/or to include the gene content of the surrounding 100 kb for clinical/molecular interpretation.…”
Section: Discussionsupporting
confidence: 55%
“…Precise mapping of CNVs is important when determining overlap with CNV in parents and control cohorts, as well as for determining the functional content in these regions and performing detailed genotype-phenotype correlations. Our results and those of others [Baross et al, 2007;Friedman et al, 2006;Pinto et al, 2007] indicate that further optimization of automatic copy number detection algorithms is required for optimal CNV identification and characterization via genome wide microarray platforms. At present, we suggest performing CNV identification with two software packages and/or to include the gene content of the surrounding 100 kb for clinical/molecular interpretation.…”
Section: Discussionsupporting
confidence: 55%
“…Twelve studies were identified since the publication of our previous meta-analysis. [21][22][23][24][25][26][27][28][29][30][31][32] Seven studies were conducted on patients based in the United States, [21][22][23]25,28,31,32 seven in Europe, 6,15,17,18,24,29,30 four using patients from multiple sources based in North America, South America, or Europe 19,20,26,27 and one in Japan. 16 All studies included sampling of control DNA as part of their protocol.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…16 All studies included sampling of control DNA as part of their protocol. Seven studies used a 1 Mb array for investigating the whole genome, 6,15,18 -20,22,29 four used a targeted array, 16,26,27,31 three used an oligonucleotide array with 30 -35 k resolution, 21,25,28 two studies used a 100-k array, 23,30 one used a tiling BAC array, 17 one study used both a targeted array and a 1-Mb array, 32 and another used a 1-Mb array supplemented with an additional 3000 gene and region-specific BAC clones increasing the resolution to 0.5 Mb. 24 Control samples varied from 2 to 316 normal people, whereas Menten et al 15 used samples from other patients in the cohort as controls.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…While overlap between different algorithms applied to the same sample is usually low (Redon et al, 2006), it should be noted that CNVs called by multiple algorithms are very likely to be true positives (Pinto et al, 2007;Marshall et al, 2008). Unfortunately, little has been published on direct comparisons of different CNV calling algorithms/ analyses (Baross et al, 2007;Greshock et al, 2007). It is also evident that the size, frequency, and type of CNV (gains vs. losses) are all detectable with variable power by different methods.…”
Section: Variability In Cnv 'Control' Studiesmentioning
confidence: 99%